Effect of stress on corrosion of high-purity magnesium in vitro and in vivo. (1st January 2019) - Gao, Yuanming; Wang, Lizhen; Li, Linhao; Gu, Xuenan; Zhang, Kuo; Xia, Jie; Fan, Yubo
Graphical abstract: Abstract: Magnesium-based implants are subjected to complicated stresses during implantation in the human body. The stress effects on corrosion of magnesium (Mg) in vitro were investigated in previous studies, whereas in this study, the corrosion behaviors of high-purity (HP) Mg under stress were comparatively studied in vitro in Hank's solution and in vivo in the subcutaneous environment of rats. Loading devices were designed to apply compressive stress (15.1 ± 0.5 MPa) and tensile stress (13.2 ± 0.2 MPa) on HP Mg specimens both in vitro and in vivo . Corrosion rates of HP Mg were characterized by mass and volume losses. It was shown that the applied compressive stress had no effect on in vitro corrosion behaviors and the applied tensile stress accelerated the in vitro corrosion, thereby causing severe pitting corrosions and stress corrosion cracking (SCC). However, there was no significant change for corrosion behaviors in vivo under neither compressive stress nor tensile stress. Severe pitting corrosion and SCC did not occur in vivo . Histological evaluation revealed that a fibrotic capsule induced by foreign body reaction was formed on the corrosion surfaces of HP Mg in the subcutaneous environment. It was proposed that the fibrotic capsule suppressed the effects of stress in vivo by protecting the corrosion surfaces. These results provided new insights into understanding the stress effects on the corrosion of Mg both in vitro and in vivo . Statement of Significance: Mg and its alloys have shown potential as biodegradable metallic materials. During implantation, Mg is subjected to various mechanical environments in the human body. It is necessary to have a clear understanding of different effects of stress on Mg corrosion. However, few studies were performed in vivo . It is important to analyze the effect of quantitative stress on Mg corrosion in vivo . Therefore, in this study, quantitative stresses were applied on Mg both in vitro and in vivo . The effects of stress on in vitro and in vivo corrosions of Mg were investigated and compared.